Disease Profile and Socio-economic Status of Patients Attending at Endocrine Outpatient Department of a Tertiary Level Hospital - Mannan, Md Abdul; Hossain, Kazi Jahangir; Kamal, Md Mustafa (Journal of Medicine, 2010)
The aim of this study was to find out the pattern of endocrine diseases and socioeconomic status of the patients attending at outpatient department of endocrinology of Sir Salimullah Medical College Mitford Hospital, Dhaka. A total of 498 endocrine patients were selected on the basis of defined criteria from September 2007 to August 2008. Of the 498 patients, 292 were female and 206 male. Majority of female patients were housewives (86.3%) while most of the male patients were businessmen (86.4%). Majority of them (59.4%) were in the age range of 41-75 years and 92.0% were married. About 7% were found obese, comparatively more in male patients. In endocrine disease pattern, 36.9% had diabetes mellitus, 18% hypothyroidism and 6.0% goiter. Impaired glucose tolerance (IGT), hyperthyroidism, hirsutism, gynaecomastia, infertility, gestational diabetes mellitus (GDM), hyperprolactinemia and short stature were found in 2.0%, 1.6%, 1.6%, 1.2%, 0.8%, 0.8%, 0.4% and 0.4% respectively. About 30.0% of the endocrine patients were found to be associated with other non-endocrine diseases or obesity. Appropriate medical treatment facilities in combination with motivational enhancement therapies are needed to ensure proper medical management of these patients. Keywords: Endocrine disease, endocrine system disease, socioeconomic status. DOI:10.3329/jom.v11i1.4264 J Medicine 2010: 11: 24-27